Lean thinking contribution to domestic food waste - Sousa, Nuno Miguel Alves (2024)
In today’s environment, marked by increasing concerns about sustainability and efficiency, households face numerous challenges related to food waste. To address this issue, it is essential for homes to adopt clear strategies for reducing waste, and effective management methodologies are crucial for this. These approaches not only help manage the complexities of food waste but also enable better adaptation to change and the maximization of opportunities for more sustainable food practices. Notable examples, such as the use of efficient food preservation practices, highlight the growing demand for and application of methodologies that promote waste reduction in various contexts. This study aims to analyze the application of Lean thinking as a methodology for reducing food waste in domestic settings. Lean thinking, known for its emphasis on waste elimination and continuous improvement, can be applied in conjunction with food conservation practices, offering an integrated approach to tackling the issue. Twelve interviews were conducted with individuals of varying ages, professions, and lifestyles. The results of this study show that applying Lean thinking can overcome the limitations of traditional food conservation practices. Furthermore, this methodology offers promising advantages for reducing food waste, benefiting not only environmental sustainability but also promoting efficiency and innovation in the management of food resources at the household level.